(untitled) (Gaceta Técnica, 2023)
This study aims to compare the structural contribution of the granular base layer stabilized with type I Portland cement versus CSS-1H cationic asphalt emulsion on roads of the Micaela Bastidas housing complex, whose area corresponds to Enlace I, II, III, IV Stage and in UPIS Villa Hermosa, Veintiséis de Octubre district, department of Piura, province of Piura. As part of the analysis, laboratory tests were carried out on the granular material extracted from the Bastian quarry, in order to obtain the characteristics of the base material. In such a way, that for the comparative evaluation of the structural contribution of the granular base, the calculation of the design for flexible pavements was executed according to the AASHTO 93 method; according to the road manual section soils and pavements, stabilized with Portland cement type I, cationic asphalt emulsion CSS-1H and without stabilization. The results obtained indicated that according to the estimated dosages at 3%, 5% and 7% of cement addition and the asphalt emulsion improves the conditions of the granular base material. In conclusion, according to the evaluation of the structural contribution, type I Portland cement is the stabilizing agent with the best behavior, even in very low dosages, which translates into pavements of competent thicknesses in construction practice